Phosphorylation of Nuclear MyoD Is Required for Its Rapid Degradation - Song, An (American Society for Microbiology, 1998)
MyoD is a basic helix-loop-helix transcription factor involved in the activation of genes encoding skeletal muscle-specific proteins. Independent of its ability to transactivate muscle-specific genes, MyoD can also act as a cell cycle inhibitor. MyoD activity is regulated by transcriptional and posttranscriptional mechanisms. While MyoD can be found phosphorylated, the functional significance of this posttranslation modification has not been established. MyoD contains several consensus cyclin-dependent kinase (CDK) phosphorylation sites. In these studies, we examined whether a link could be established between MyoD activity and phosphorylation at putative CDK sites. Site-directed mutagenesis of potential CDK phosphorylation sites in MyoD revealed that S200 is required for MyoD hyperphosphorylation as well as the normally short half-life of the MyoD protein. Additionally, we determined that turnover of the MyoD protein requires the proteasome and Cdc34 ubiquitin-conjugating enzyme activity. Results of these studies demonstrate that hyperphosphorylated MyoD is targeted for rapid degradation by the ubiquitin pathway. The targeted degradation of MyoD following CDK phosphorylation identifies a mechanism through which MyoD activity can be regulated coordinately with the cell cycle machinery (CDK2 and CDK4) and/or coordinately with the cellular transcriptional machinery (CDK7, CDK8, and CDK9).